Overview of physicochemical properties of nanoparticles as drug carriers for targeted cancer therapy - Yagublu, Vugar; Karimova, Aynura; Hajibabazadeh, Javahir; Reißfelder, Christoph; Muradov, Mustafa; Bellucci, Stefano; Allahverdiyev, Adil (Journal of Functional Biomaterials, 2022)
The advent of nanotechnology has brought about revolutionary innovations in biological research techniques and medical practice. In recent years, various “smart” nanocarriers have been introduced to deliver therapeutic agents specifically to the tumor tissue in a controlled manner, thereby minimizing their side effects and reducing both dosage and dosage frequency. A large number of nanoparticles have demonstrated initial success in preclinical evaluation but modest therapeutic benefits in the clinical setting, partly due to insufficient delivery to the tumor site and penetration in tumor tissue. Therefore, a precise understanding of the relationships betweenthe physicochemical properties of nanoparticles and their interaction with the surrounding microenvironment in the body is extremely important for achieving higher concentrations and better functionality in tumor tissues. This knowledge would help to effectively combine multiple advantageous functions in one nanoparticle. The main focus of the discussion in this review, therefore, will relate to the main physicochemical properties of nanoparticles while interacting within the body and their tuning potential for increased performance.